The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.2217/bmm-2021-0108
|View full text |Cite
|
Sign up to set email alerts
|

Novel Molecular Biomarkers and Diagnosis of Acute Appendicitis in Children

Abstract: Reliable and efficient diagnosis of pediatric appendicitis is essential for the establishment of a clinical management plan and improvement of patient outcomes. Current strategies used to diagnose a child presenting with a suspected appendicitis include laboratory studies, clinical scores and diagnostic imaging. Although these modalities work in conjunction with each other, one optimal diagnostic strategy has yet to be agreed upon. The recent introduction of precision medicine techniques such as genomics, tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 79 publications
0
11
0
3
Order By: Relevance
“…As suggested in a recent review, the management in the ED would be improved, and the efficiency of AA diagnosis would be increased with a diagnostic tool developed with the biomarker technology. [10] The elevated levels of CRP, WBC were consistently demonstrated to be a significant indicator for AA diagnosis. The researchers indicated that WBC and Neu had higher sensitivity early in the disease, while the sensitivity of CRP increased with the progression and reached its highest sensitivity at day four.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…As suggested in a recent review, the management in the ED would be improved, and the efficiency of AA diagnosis would be increased with a diagnostic tool developed with the biomarker technology. [10] The elevated levels of CRP, WBC were consistently demonstrated to be a significant indicator for AA diagnosis. The researchers indicated that WBC and Neu had higher sensitivity early in the disease, while the sensitivity of CRP increased with the progression and reached its highest sensitivity at day four.…”
Section: Discussionmentioning
confidence: 93%
“…[16] On the other hand, the low specificity of CRP for AA was recently underlined, and its limited utility as a diagnostic biomarker was emphasized. [10,17] Plasma levels of IL-6, CRP, and PCT were significantly different in children with AA compared to children with non-AA causes of abdominal pain. [18] The overall performance of IL-6 has been reported to be superior to PCT, especially regarding cost, sensitivity, and prediction of perforation.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…More research is needed when it comes to biomarkers; it is probably more likely than one or more biomarkers should be incorporated into the clinical scoring systems rather than be used independently. Precision medicine techniques also have the potential to add to the strength of the diagnostics [ 17 ].…”
Section: Resultsmentioning
confidence: 99%
“…However, despite its high incidence the accurate preoperative diagnosis of AA is still challenging. The negative appendectomy rate is 20.6% [2] with peaks in certain categories of patients such as women in childbearing age (30-50%) or young children (30-46%) [3,4]. The diagnosis of AA is still predominantly clinical with 80% diagnostic accuracy of the initial algorithm consisting of suggestive history,pain at Mc-Burney's point and leukocytosis [5].…”
Section: Introductionmentioning
confidence: 99%